An Early Detection-Warning System to Identify Speed Breakers and Bumpy Roads using Sensors In Smartphones - Vamsee Krishna Kiran M; Vimalkumar K; Vinodhini R E; Archanaa R (Institute of Advanced Engineering and Science, 2017)
Speed breakers and bumpy roads are a major threat to drivers that questions their safety. The mishap happens because of no sign boards indicating the speed breaker, poor visibility at night and road works that are often carried out with no proper signs of road deviations and also the negligence of the driver. All these factors put the life of the persons in vain causing damage to the vehicle as well as life. Also, bumpy roads have become a problem for cars with less ground clearance. The focus of the paper is on designing an early warning system detecting both speed breaker humps and bad road conditions. The approach used in this paper is a real-time solution and is developed as an android service that runs in the background and relies on Google Maps application in the smartphone. This service will throw an alert giving early warning if the user is approaching the speed breaker or a bumpy road. Apart from just giving an early alert to the user, it also provides the user with an alternative and a better route. The solution proposed in this work is a form of crowdsourcing where users share and get data, therefore making the system cost effective.